DETEKSI SENYAWA ISOFLAVON DAIDZEIN DAN GENISTEIN PADA KULTUR IN-VITRO KALUS KEDELAI (Glycine Max Merr.) - Tintrim Rahayu (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2012)
The aim of this research is to identify the isofl avon compounds in the in-vitro cultured callus of soybean (Glycine max Merr.). This is an explorative research, in which callus were cultured in the B5 medium supplemented with 2 ppm 2,4 D. The friable callus were found when it was cultured in the solid medium containing 8 g/l agar and 20 g/l sucrose. When the callus and soybean were extracted with ethanol, a yellow colored substance appeared. If further analysis was done with thin layer chromatography (TLC) method employing 0,2 mm thin layer silica gel 60 F254 (DC-Plastikfolien Schicht-dicke), and eluent consisting n-Butanol - HCL 0.1 N (1:1), six light bluecolor nodes appeared under 366 nm UV light. The nodes have the following Rf: 0,14; 0,30; 0,52; 0,63; 0,79 and 0,92 respectively. This TLC result is comparable with the TLC result from soybeans since they have two nodes with the same Rf and color, namely blue color at Rf 0,81 and 0,92 respectively. Further confi rmation using HPLC (High Performance Liquid Chromatography) equipped with UVvis detector and Lichrospher 100RP–18, (10 μm) colom, as well as Hitachi D–2500 Chromato-integrator indicated that those similar two nodes identifi ed in the TLC were either daidzein or genistein. They can be detected by HPLC at 250 nm and 260 nm, when theywere eluated at the 80% metanol. The HPLC quantitative calculation indicated that concentration of daidzein is four time higher as it was compared with the daidzein concentration in the bean. The concentration of daidzein in the callus remained high up to 4–5 weeks after plantation. It’s concentration will decrease when the callus reached 6 weeks after plantation. Genistein as another component of isoflavon is not appear upon callus, while on soybean seeds extracts, both daidzen and genistein are detected.